Competition enforcement and regulatory alternatives. Issue 4 (28th December 2021) - Akhgar, Thomas; Braham, David du Parc
Abstract : The concurrency arrangements under the Competition Act 1998, which enable the sector regulators to enforce ex post competition law alongside their ex ante regulatory powers, aim to promote competition across the regulated sectors. As well as this well-established arrangement, following a range of reports indicating the limitations of ex post competition enforcement in digital markets, the Competition and Markets Authority has more recently taken on a new role in relation to pro-competitive regulation in digital markets, expanding its remit to a new regulatory function. This article considers the UK's approach of applying the right balance of competition enforcement and regulatory alternatives to ensure competition is promoted via the most effective means possible.